The Covid-19 explosion in the state of Amapá: how is the most preserved region in the Brazilian Amazon currently fighting the SARS-COV 2 pandemic? - Coelho Paraguassu, Eber; Celis de Cardenas, Anneli Mercedes; Ferreira de Andrade, Rosemary; La Vecchia, Carlo; Naldi, Luigi (Brazilian Journal of Implantology and Health Sciences, 2020)
The state of Amapá is located in the extreme north of Brazil, within the Amazon rainforest and is crossed by the Equator. It has a hot and humid climate with rains that last 8 months a year and 4 months of unrelenting sun that melts rubber from car seals, fries eggs on the floor and even cooks a whole egg tub, in case you forget in a car exposed to the sun . It was believed that with this potent solar incidence, the Sars-COV 2 virus would not have so much impact in this region, a terrible mistake! Today Amapá has the highest incidence of Covid-19 in the whole of Brazil, with a maid of 600 cases per hundred thousand inhabitants and in the Amazon it is the 3rd in deaths and loses in this item only to the state of Amazonas and Pará.